2012
DOI: 10.1038/onc.2012.136
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase-4 promotes proliferation and angiogenesis of lung cancer by crosstalk with HIF

Abstract: Lung cancer is the leading cause of cancer death worldwide. Recent data suggest that cyclic nucleotide phosphodiesterases (PDEs) are relevant in various cancer pathologies. Pathophysiological role of phosphodiesterase 4 (PDE4) with possible therapeutic prospects in lung cancer was investigated. We exposed 10 different lung cancer cell lines (adenocarcinoma, squamous and large cell carcinoma) to hypoxia and assessed expression and activity of PDE4 by real-time PCR, immunocytochemistry, western blotting and PDE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
84
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(86 citation statements)
references
References 32 publications
1
84
0
1
Order By: Relevance
“…3). The H1975 cell line, which overexpresses PDE4, was highly sensitive to the PDE4 inhibitor rolipram (21), suggesting that the use of PDE4 inhibitors in conjunction with EGFR TKIs could represent a novel synthetic lethality approach (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3). The H1975 cell line, which overexpresses PDE4, was highly sensitive to the PDE4 inhibitor rolipram (21), suggesting that the use of PDE4 inhibitors in conjunction with EGFR TKIs could represent a novel synthetic lethality approach (19).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphodiesterases 4 (PDE4) isoforms A and D inhibit protein kinase A (PKA), a main cAMP effector, and activate ERK (ref. 21; Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a previous study using a sleeping beauty transposon-based screen suggested that PDE4D might function as a proliferation promoting factor in prostate cancers (12). Very recently, Pullamsetti et al found that cross-talk that occurred between PDE4 and hypoxia induciblefactor signaling might promote angiogenesis in lung cancer (13). However, the tumor-specific alterations in PDE4D genome and function are not well elucidated.…”
mentioning
confidence: 97%
“…PDE4D was reported to be overexpressed in human prostate cancers and associated with increased tumor growth and cell migration (39). PDE4D is also expressed in lung cancer, interacting with hypoxia-inducible factor (HIF) signaling and promoting lung cancer progression (40). PDZK1IP1 was shown to be overexpressed in a variety of human cancers in the kidney, colon, lung, and breast (41).…”
Section: Discussionmentioning
confidence: 99%